Evaluation of Chronic Physical and Psychological Stress Induction on Cardiac Ischemia / Reperfusion Injuries in Isolated Male Rat Heart: The Role of Sympathetic Nervous System - Kamran Rakhshan; Alireza Imani; Mahdieh Faghihi; Fatemeh Nabavizadeh; Masoumeh Golnazari; SeyedMorteza Karimian (Acta Medica Iranica, 2015)
Exposure to stress leads to physiological changes called “stress response” which are the result of the changes in the adrenomedullary hormone system, hypothalamus-pituitary-adrenal (HPA) and sympathetic nervous system (SNS) activity. In the present study, the effects of chronic physical and psychological stress and also the role of sympathetic system effects in stress on ischemia/reperfusion (I/R) injuries have been= studied in isolated rat heart. Rat heart was isolated and subjected to 30 min regional ischemia and 120 min reperfusion. The daily stress was induced for one week prior to I/R induction. Sympathectomy was done chemically by injection of hydroxyl-dopamine prior to stress induction. There were no significant changes in heart rate and Coronary Flow between groups. Left ventricular developed pressure (LVDP) and rate product pressure (RPP) in both physical and psychological stress groups decreased significantly compared to those in control group (P<0.05), but there was no significant difference betwe n physical and psychological stress groups. Infarct size significantly increased in both physical and psychological stress groups and control group (P<0.05. Sympathectomy before induction of stress led to the elimination of the deleterious effects of stress as compared with stress groups (P<0.05). These results show that induction of chronic physical and psychological stress prior to ischemia/reperfusion causes enhancement of myocardial injuries and it seems that increased sympathetic activity in response to stress is responsible for these adverse effects of stress on ischemic/reperfused heart.